PREVALENSI POST-TRAUMATIC STRESS DISORDER (PTSD) DI ANTARA PERAWAT PASCA TERKONFIRMASI COVID-19 DI PROVINSI SUMATERA UTARA - Tambunan, Dior Manta; Banjarnahor, Seriga (Indonesian Trust Health Journal, 2023)
Post-Traumatic Stress Disorder (PTSD) is a mental disorder that can occur as a result of direct or indirect contact with a traumatic event. The possibility of PTSD for nurses in the Covid-19 isolation room is the lack of staff which causes the nurse's working day to be longer, the lack of support and compensation from the organization. The current study aims to identify the prevalence of PTSD among post-confirmed Covid-19 nurses in North Sumatra Province. This study used a cross sectional study through a survey. This research was conducted from March to June 2022. The study population was all nurses who were confirmed to have Covid-19 in North Sumatra Province. The sampling technique is total sampling. The instrument was adopted from The PTSD Checklist for DSM-5 with Life Events Checklist for DSM-5 and Criterion A. This study used univariate statistical tests. The results of this study indicate that the distribution of the frequency of occurrence of PTSD with a Likert scale is not at all with a percentage of 47.1%, followed by a little bit with a frequency of 26.5%, while Extremely with a presentation of 5.4%. While the average value of the prevalence of PTSD in nurses after confirming Covid-19 in respondents as many as 509 nurses was not indicative of PTSD with an average value of 20.5. So, it was concluded that there was no indication of PTSD in nurses after confirmed Covid-19. It is recommended for future researchers to conduct qualitative research on PTSD experiences of nurses after confirmed Covid-19 and more specific research samples in special rooms that treat Covid-19 isolation patients. Abstrak Post-Traumatic Stress Disorder (PTSD) adalah gangguan mental yang dapat terjadi akibat kontak langsung atau tidak langsung dengan peristiwa traumatis. Kemungkinan terjadinya PTSD untuk perawat di ruang isolasi Covid-19 adalah kurangnya staf yang menyebabkan lama hari kerja perawat makin panjang, kurangnya dukungan dan kompensasi dari organisasi. Studi saat ini bertujuan untuk mengidentifikasi prevalensi PTSD di antara perawat pasca terkonfirmasi Covid-19 di Provinsi Sumatera Utara. Penelitian ini menggunakan studi Cross Sectional melalui survei. Penelitian ini dilakukan bulan Maret – Juni 2022. Populasi penelitian adalah seluruh perawat yang terkonfirmasi Covid-19 di Provinsi Sumatera Utara. Teknik Pengambilan sampel adalah total sampling. Instrumen diadopsi dari The PTSD Checklist for DSM-5 with Life Events Checklist for DSM-5 and Criterion A. Penelitian ini menggunakan uji statistik univariat. Hasil penelitian ini menunjukkan bahwa distribusi frekuensi terjadinya PTSD dengan skala likert adalah tidak sama sekali dengan presentase 47,1%, disusul oleh sedikit dengan frekuensi 26,5%, sementara sangat banyak dengan presentasi 5,4%. Sementara nilai rata-rata prevalensi terjadinya PTSD pada perawat pasca perkonfirmasi Covid-19 pada responden sebanyak 509 orang perawat adalah tidak terindikasi PTSD dengan nilai rata-rata 20,5. Maka disimpulkan bahwa tidak ada indikasi PTSD pada perawat pasca terkonfirmasi Covid-19. Direkomendasikan kepada peneliti selanjutnya agar melakukan penelitian secara kualitatif tentang pengalaman PTSD perawat pasca terkonfirmasi Covid-19 dan sampel penelitian lebih spesifik lagi di ruang khusus yang merawat pasien isolasi Covid-19.